The political economy of enhancing children's rights through mineral rents: The case of Mongolia - Pascale Hatcher; Etienne Roy Grégoire; Bonnie Campbell (United Nations Research Institute for Social Development (UNRISD), 2016)
Populated by predominantly young people, Mongolia's economy has relied heavily in recent years on mining. After several years of boom, the recent decrease in mining rents has only emphasized the pressing need for linking mining revenues to continuing demands in social expenditure, especially in ways that promote the rights of the child. While geared at attracting foreign investors for large-scale mining activities, the more liberal norms adopted by Mongolia since its political transition may have hampered the implementation of a development model informed by a rights-based approach. Moreover, the particular set of norms driving Mongolia's mining boom appears to be displacing, at least partially, the policy debates over the country's mining governance to the transnational level. In turn, such trends seem to explain why local and national socio-environmental issues pertaining to the sector have at times been addressed in technocratic terms that cannot easily conform to a rights approach. The paper reviews the historical progression of the country's mining regime and its contribution to government revenues, analyses the linkages between mining rent and social expenditure, focusing on children and the extractive sector's ability/willingness to take account of children's rights in the small-scale and artisanal mining (SSAM) sector. It concludes that Mongolia should establish a coherent long-term poverty reduction strategy that encompasses both the economic benefits and potential harm of extractive industries; strengthen socio-environmental regulation and enforcement capacity: ratify and apply international instruments regarding access to information, public participation in decision making, and access to justice in environmental matters: put in place effective prevention and remedy mechanisms for human rights abuses by private companies; and pursue its efforts towards the legalization, regulation and monitoring of SSAM using a rights-based approach.
Additional information: Prepared for the UNRISD/UNICEF project on Mobilizing Revenues from Extractive Industries: Protecting and Promoting Children's Rights and Well-Being in Resource-Rich Countries
Keywords: 330